Gramatica limbii române în veșminte noi: Romanian grammar’s new clothes - Ciortea, Marcela (Swedish Journal of Romanian Studies, 2021)
In 2005, The Romanian Academy published a new Romanian Language Grammar, four decades after the last edition of the previous Grammar. The event sparked a lot of controversy, even indignation, especially among those familiar with the old grammar and unwilling to embrace the interpretations of a new one. Only five years after this publication, a group of researchers separated themselves from the 2005 edition’s authors and clustered around Professor Gabriela Pană Dindelegan, into a team of scholars who undertook the toilsome mission of aligning the Romanian grammar to the European research manner. The list of these works, purposefully set up in chronological order, offers on overall view of the researcher groups that have put an effort in this direction over the last ten years. The present paper addresses both the Romanian native speakers and those interested in the grammar of this language. It brings under scrutiny three segments: the pronominal clitics, verb voices and the prepositional complement.